METONIMIA KONSEPTUAL DALAM AL-QURAN: ANALISIS KOGNITIF MAKNA WAJH DAN YAD - Inayatusshalihah Inayatusshalihah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
Metonymy in the traditional view is the referring an entity with another word that has a meaning relation with the word referring to that entity. While in the view of cognitive linguistics, metonymy is regarded as a cognitive tool for conceptualization an entity through another entity. Using the data sourced from twenty surah of The Quran, this paper aims to explain the meaning of conceptual metonymy in The Quran using human body-related terms especially word wajh ‘face’ and yad ‘hand’. The study was based on general conceptual metonymy theory. In those 20 surahs, found 20 verses using word wajh and 24 verses using word yad. Based on analysis, word wajh referred to person, God’s substance, and pleasure. Word yad referred to meaning of person, power, authority, fingers and palm, and miserly. The metonymic concepts used were part for whole, whole for part, place for what located there, and cauce for effect.